A transição neoproterozoico-eopaleozoico no Graben Pimenta Bueno, NW da bacia dos Parecis, estado de Rondônia - AFONSO, Jhon Willy Lopes (Universidade Federal do Pará, 2019)
The Pimenta Bueno Graben (PBG) represents a sub-basin localized at northwestern portion of the Parecis Basin, established over the southwestern of Amazon Craton. The PBG is filled by a succession of siliciclastic rocks, and subordinately carbonate rocks with approximately 1000 m of thick on subsurface. The Paleozoic siliciclastic succession exposed in PBG overlay crystalline basement rocks and carbonatic-siliciclastic deposits which were previously considered as Paleozoic age. Outcrop-based facies and stratigraphic analysis around the cities of Cacoal, Pimenta Bueno and Espigão d'Oeste, Rodônia State, allowed the redescribing and redefinition of PBG basal units, previously included in the Cacoal and Pimenta Bueno formations. The Cacoal Formation unconformably overlies Precambrian crystalline basement rocks. This was redefined in two units: one homonymous, which was characterized by diamictite and sandstones, and another named Espigão d'Oeste Formation, interpreted as a Neoproterozoic cap carbonate, consisting of pinkish dolomite, dolomite-siltstone rhythmite and a thick siltstone sucession. Both units were inserted in the base of the Ediacaran, and related, respectively, to the glacial and post-glacial global Marinoan event (635 Ma) linked to the hypothesis of Snowball-Slushball Earth. These units belong to basement coverage of PBG, unrelated with the Paleozoic succession of the Parecis Basin. The pink dolomites were interpreted as Neoproterozoic cap carbonates unconformably overlain by Ordovician-Silurian Pimenta Bueno Formation. Twenty sedimentary facies grouped in eight facies associations (FA) have been interpreted as glacial-marine, carbonate and siliciclastic platform and coastal deposits. The glacio-marine deposits (AF1) of Cacoal Formation consist of diamictite containing faceted and striated clasts (blocks and pebbles of granite, gneiss, volcanic rock, phyllite, sandstone, pelite and chert), interbedded with fine- to medium grained sandstones, which consists of climbing ripple cross-laminated and rare dropstones. The cap carbonate includes two facies associations, AF2 and AF3. The AF2 consist pinkish finely laminated doloboundstones and dolomudstones/dolopackstones with abundant micro and macropelóides. This association was deposited in wave-influenced shallow marine platform grading towards the top to lagoonal dolostone/siltstone rhythmites (AF3). The δ13C values among - 3.66 to – 3.03 ‰ founded in AF2 and AF3 are typical of Marinoan cap carbonate. Eosilurian Pimenta Bueno Formation consists by massive diamictite and pelites with dropstones occurring interbedded with sigmoidal cross-bedded sandstone, punctually containing dump structure. This succession is organized in coarsening and thickening upward cycles interpreted as advance and retreat deposition of coastal glaciers and melt-out deltas (AF4). The post-glacial sea level rise allowed the installation of wave- and storm-influenced siliciclastic platform consisting by hummocky cross-stratified sandstone and laminated mudstones (AF5), as well as, shoreface deposits (AF6) indicated by swaley cross stratified fine- to medium-grained sandstone. Cross-bedded sandstone with mud drapes in the foresets and sandstone-pelite rhythmite suggest deposition in subtidal zone (AF7). Tidal processes in this facies indicate probable oceanic connection with Silurian sea almost devoid of glacial influence. Laminated mudstones and massive sandstone with cross lamination, locally bioturbated by Skolithos, organized in coarsening upward cycles indicate progradation of suspended lobes in lakes or restricted sea (AF8). The recurrence of glacial events in the studied succession indicates extreme climatic conditions of Snowball-Slushball Earth expanding for the more southwestern portion of Amazonian Craton during the Neoproterozoic. The glaciers returned to this part of Amazonia only in the end of Ordovician with important records in the Brazilian intracratonic basins.